EFEKTIVITAS PROGRAM KARTU INDONESIA PINTAR KULIAH (KIP-K) DI UNIVERSITAS PEMBANGUNAN NASIONAL “VETERAN” JAWA TIMUR - Ellza Nathania Christy; Riena Latifa; Nursavita Purwatitisari; Putri Aprilia Regina Prabowo; Bagus Nuari Harmawan (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
Abstrak UPN “Veteran” Jawa Timur is one of the universities that provides KIP Kuliah assistance for its students from the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. This research aims to determine the effectiveness of the KIP Kuliah program at UPN